2019
DOI: 10.1016/j.conbuildmat.2019.03.060
|View full text |Cite
|
Sign up to set email alerts
|

In-plane elastic flexibility of cross laminated timber floor diaphragms

Abstract: In-plane Elastic Flexibility of Cross Laminated Timber Floor Diaphragms This is the author's postprint. The published article is: D'Arenzo, G. et al. (2019) 'In-plane elastic flexibility of cross laminated timber floor diaphragms', Construction and Building Materials. Elsevier Ltd, 209, pp. 709-724. dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In joints with small friction (such as those in CLT floors), sliding between the CLT panels might occur for service dynamic loadings. According to the laboratory tests presented by Brandner et al (2017), D'Arenzo, Casagrande, Reynolds, andFossetti (2019), Oh et al (2017) and Yasumura, Kobayashi, Okabe, Miyake, and Matsumoto (2016), the connections influence the in-plane stiffness of CLT floors and walls. Moreover, this stiffness is non-trivially dependent on several other factors, such as panel fabrication, boundary conditions affecting the development of shear mechanism, and the number and orientation of panels in a composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In joints with small friction (such as those in CLT floors), sliding between the CLT panels might occur for service dynamic loadings. According to the laboratory tests presented by Brandner et al (2017), D'Arenzo, Casagrande, Reynolds, andFossetti (2019), Oh et al (2017) and Yasumura, Kobayashi, Okabe, Miyake, and Matsumoto (2016), the connections influence the in-plane stiffness of CLT floors and walls. Moreover, this stiffness is non-trivially dependent on several other factors, such as panel fabrication, boundary conditions affecting the development of shear mechanism, and the number and orientation of panels in a composition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this stiffness is non-trivially dependent on several other factors, such as panel fabrication, boundary conditions affecting the development of shear mechanism, and the number and orientation of panels in a composition. Studies by Ashtari, Haukaas, andLam (2014) andD'Arenzo et al (2019) concluded that the sliding between the panels is the main factor contributing to the in-plane flexibility of CLT floors.…”
Section: Introductionmentioning
confidence: 99%
“…A rigid diaphragm transmits loads to supports in proportion to the stiffness of the supports, whereas flexible diaphragms deformed in-plane through bending [2]. The lateral load distribution is influenced by the material properties and the load-slip behaviour of the connections between the adjacent panels (called panel-to-panel connections) and panel-to-beam connections [3]. Beairsto, in 2020 [4], evaluated the ductility of two large CLT diaphragms under monotonic and cyclic loads.…”
Section: Introduction 456mentioning
confidence: 99%
“…For a modular steel-timber composite floor, Cristiano Loss [10][11][12] analyzed and studied the in-plane stiffness and bearing capacity of the floor system, and some relevant design suggestions are put forward. D' Arenzo G et al [13]proposed an equivalent frame model to model the in-plane deformation characteristics of prefabricated wooden floor, which can quickly obtain the in-plane stiffness of the floor. Ma Zhong et al [14]pointed out that the assembly direction has a great influence on the mechanical performance of floor,compared with loading parallel to joist, loading perpendicular to joist could greatly facilitate the floor system to achieve higher strength and in-plane rigidity , but all of the values of in-plane rigidity were lower than 10kN/mm under both loading modes.…”
Section: Introductionmentioning
confidence: 99%